(untitled) (Interdisciplinary Studies Journal, 2025)
With the main objective of analyzing the incorporation of Special Education into the Political-Pedagogical Project (PPP) of a municipal public elementary school from an inclusive perspective, a qualitative, exploratory-descriptive methodology was adopted, based on bibliographic research and documentary analysis of the PPP. An analytical framework adapted from current literature was used as a theoretical-methodological reference. The results indicated that, although the institutional document mentioned the principles of Special Education and inclusion, its approach was superficial. No effective articulation with concrete pedagogical practices or specific action plans for the target audience of Special Education was found. There was also a lack of specific methodological guidelines aimed at this group, as well as the absence of differentiated assessment strategies. It is concluded, therefore, that the incorporation of Special Education into the PPP remains a challenge in the analyzed school context. Structural, conceptual, and formative reformulations are necessary to align normative discourse with effective educational practices.